A privacy protection scheme for electricity transactions in the microgrid day-ahead market based on consortium blockchain. (October 2022) - Wang, Baoyi; Liu, Hongchen; Zhang, Shaomin
Highlights: A privacy protection scheme for microgrid day-ahead market is proposed. ElGamal algorithm is adopted to generate anonymous identities that can be traced. Certificateless signcryption is improved to make the scheme more secure and efficient. The consortium blockchain is adopted to make trading more secure and efficient. Abstract: The electricity trading plan made by the users in the microgrid day-ahead market (DAM) contains the electricity consumption information of the future day. Aiming at the problem that the leakage of electricity consumption information threatens the privacy security of users and the leakage of electricity trading plan destroys the fairness of the DAM, a privacy protection scheme for electricity transactions in microgrid DAM based on consortium blockchain is proposed. Firstly, the scheme is based on the ElGamal algorithm that generates anonymous identities for users involved in transactions, preventing leakage of electricity consumption information and allowing the real identity of the fraudster to be traced in the event of fraudulent transactions. Secondly, a certificateless signcryption (CLS) algorithm is improved to realize the encryption and authentication of the user's electricity trading plan, which enhances the efficiency of the scheme. Finally, the scheme realizes decentralized trading of users in the microgrid in the DAM through the consortium blockchain and smart contracts, ensuring transaction security and improving transaction efficiency. The scheme is proved to have high security under different types of attacks by stochastic prediction machine model. Moreover, by calculating the computation time for different kinds of operations in the two stages of signcryption and unsigncryption, it is concluded that the computation cost of this scheme is lower than that of other schemes of the same type has higher efficiency.